Attitudes and Anxiety to the Acceptance of the Covid-19 Vaccine During Pregnancy - Tauho, Kristiani Desimina; Marques, Isaias Da Costa (JENDELA NURSING JOURNAL, 2024)
Background: pregnant women have a higher risk of experiencing severe complications related to Covid-19. For this reason, vaccination is essential to do. However, it was reported that 79.2% of pregnant women were unsure about getting vaccinated, and even 78.4% were worried about the side effects.Purpose: this research was conducted to determine the effect of knowledge, attitudes, and anxiety of pregnant women on receiving COVID-19 vaccination.Methods: using a quantitative method with a correlational type, as many as 40 pregnant women in the second and third trimesters were selected to be involved by Accidental Sampling.Results: the results showed that 90% of respondents had sufficient knowledge, 80% had a good attitude, 77.5% of pregnant women had severe anxiety, and 85% accepted the vaccination. Based on the multiple linear correlation test, the influence of knowledge, attitude, and anxiety on the acceptance of the Covid-19 vaccination was 0.049, 0.000, and 0.526, respectively. Partial regression analysis for each independent variable shows only the t count t table value for the knowledge and attitude variables.Conclusion: the higher the level of knowledge and the more willing pregnant women are to receive vaccinations, the higher the acceptance of COVID-19 vaccination during pregnancy.